2017
DOI: 10.29121/granthaalayah.v5.i5.2017.1856
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Characteristics and Competencies as Determinants of Corporate Performance: A Study on Small Enterprises in Mogadishu, Somalia

Abstract: The encouraging outcomes of organizational success, emerging from productive entrepreneurship has led academic and administrative attention on concepts of entrepreneurial competencies and entrepreneurial characteristics in the last few decades. In Somalia particularly, the women have been found to be playing a significant role in the small business sector, despite the several challenges faced by them. The present research aims at assessing the effect of entrepreneurial competencies and entrepreneur’s demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
6
18
0
1
Order By: Relevance
“…From the estimated regression model, a one unit standard deviation increase in the PMSE firms causes 0.087 standard deviation increase in the age of respondents keeping all other factors constant. The finding of this study was in line with the work of (Mahadalle & Kaplan, 2017) that found the age of the MSE firm owner is positively associated with performance of the MSE firms in Somalia. Another study conducted by (Gerli, Gubitta, & Tognazzo, 2011) also supports the finding of this study in which they have found that the age of the MSE owner was positively related to the performance of the MSE firms in Italy.…”
Section: The Nature Of Taxation and The Types Of Tax Paid By The Mse supporting
confidence: 91%
See 4 more Smart Citations
“…From the estimated regression model, a one unit standard deviation increase in the PMSE firms causes 0.087 standard deviation increase in the age of respondents keeping all other factors constant. The finding of this study was in line with the work of (Mahadalle & Kaplan, 2017) that found the age of the MSE firm owner is positively associated with performance of the MSE firms in Somalia. Another study conducted by (Gerli, Gubitta, & Tognazzo, 2011) also supports the finding of this study in which they have found that the age of the MSE owner was positively related to the performance of the MSE firms in Italy.…”
Section: The Nature Of Taxation and The Types Of Tax Paid By The Mse supporting
confidence: 91%
“…That is, male owned MSE firms may advance in the performance of the MSE firms better than female owned PMSE firms in the study area. The result of this study was supported by the work of (Mahadalle & Kaplan, 2017) that found the gender of the MSE owners is positively associated with the performance of MSE firms in Somalia. Also, the finding was in line with the study conducted by (Gerli, Gubitta, & Tognazzo, 2011) that found the gender of the MSE owner is positively related to the performance of the MSE firms in Italy.…”
Section: The Nature Of Taxation and The Types Of Tax Paid By The Mse supporting
confidence: 71%
See 3 more Smart Citations